2011
DOI: 10.1136/gutjnl-2011-300719
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormone therapy and colorectal cancer risk by molecularly defined subtypes among older women

Abstract: Background Postmenopausal hormone (PMH) therapy may reduce colorectal cancer (CRC) risk, but existing data are inconclusive. Objectives To evaluate associations between PMH therapy and incident CRC, overall and by molecularly defined subtypes, in the population-based Iowa Women’s Health Study of older women. Methods Exposure data were collected from Iowa Women’s Health Study participants (55–69 years) at baseline (1986). Archived, paraffin-embedded tissue specimens for 553 CRC cases were collected and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 40 publications
5
57
1
1
Order By: Relevance
“…Concordantly, emerging data from our group and others demonstrate differential associations between common environmental exposures, including smoking, MHT and folate, and incident CRCs defined by microsatellite instability (MSI), CpG island methylator phenotype (CIMP), KRAS and BRAF mutation status (23,1518) and TP53 protein expression (19), among other phenotypic markers. Most significantly, post-menopausal MHT was associated with a lower risk for MSI-L/MSS tumors (15) and smoking was shown to be associated with MSI-high, CIMP-positive, and BRAF-mutated tumors (2). …”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Concordantly, emerging data from our group and others demonstrate differential associations between common environmental exposures, including smoking, MHT and folate, and incident CRCs defined by microsatellite instability (MSI), CpG island methylator phenotype (CIMP), KRAS and BRAF mutation status (23,1518) and TP53 protein expression (19), among other phenotypic markers. Most significantly, post-menopausal MHT was associated with a lower risk for MSI-L/MSS tumors (15) and smoking was shown to be associated with MSI-high, CIMP-positive, and BRAF-mutated tumors (2). …”
Section: Introductionsupporting
confidence: 70%
“…smoking, MHT, and folate were investigated as potentially modifiable lifestyle, medication, and dietary factors, respectively. Based on previous reports from our group and others (23, 1516, 1819), these exposures may be plausibly linked to heterogeneous pathways of colorectal carcinogenesis.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Three studies observed an inverse association between menopausal hormone therapy use and microsatellite stable colorectal cancer (18)(19)(20), whereas another study reported differing associations (21). Whether ESR2 expression in colorectal cancer is associated with microsatellite status remains to be clarified, as Wong and colleagues found that ESR2 isoform 1 expression was decreased in microsatellite stable colorectal cancer compared with microsatellite-unstable colorectal cancer, but no differences in expression were observed for isoform 2 and 5 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies investigated the association between use of menopausal hormone therapy and risk for molecularly defined subtypes of colorectal cancer (17)(18)(19)(20)(21). Three studies observed an inverse association between menopausal hormone therapy use and microsatellite stable colorectal cancer (18)(19)(20), whereas another study reported differing associations (21).…”
Section: Discussionmentioning
confidence: 99%